HUBUNGAN ASUPAN MINERAL TERHADAP KARIES GIGI PADA SISWA-SISWI KELAS IV SD SWASTA MUHAMMADIYAH 03 KELURAHAN TANJUNG REJO KECAMATAN MEDAN SELAYANG - Aritonang, Intan; Lusiani, Yetti; Hasny, Hasny (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2016)
Dental and oral health is part of physical health which cannot be separated from one another and it can affect for all people. The target of increasing dental and mouth health through group counseling activity is elementary school children since this age is social transition period when children change their behavior.The research was an analytical survey which was aim to find out the correlation between mineral intake and dental caries in Grade IV elementary students at SD Swasta Muhammnadiyah 03, Medan Selayang.This research was conducted by using subjective and objective examination on 33 students. The result of subjective examination showed intake of Mineral Nutrision performed, 8 respondents (24.24%) had good intake, 18 respondents (54.55%) had moderate intake, and 7 respondents (21.21%) had bad intake. The conclusion of the research that there is a significant relationship between the intake of minerals with dental caries student of SD Muhammadiyah 03, p worth of 0.035 for α = 0.05. To reduce the increase in the incidence of caries is increase oral hygiene, better mineral intake and perform curative action by doing fillings for Grade IV students of SD Swasta Muhammadiyah 03 Medan Selayang.